Shaking up the city : ignorance, inequality, and the urban question - Slater, Tom, 1975- (University of California Press, 2021)
"Shaking Up the City critically examines many of the concepts and categories within mainstream urban studies that serve dubious policy agendas. Through a combination of abstract theory and concrete empirical evidence, Tom Slater strives to 'shake up' mainstream urban studies in a concise and pointed fashion, turning on its head much of the prevailing wisdom in the field. In doing so, he explores the themes of 'data-driven innovation', urban 'resilience', gentrification, displacement and rent control, 'neighborhood effects', territorial stigmatization, and ethnoracial segregation. Slater analyzes how the mechanisms behind urban inequalities, material deprivation, marginality, and social suffering in cities across the world are perpetuated and made invisible. With important contributions to ongoing debates in sociology, geography, planning, and public policy, and engaging closely with struggles for land rights and housing justice, Shaking Up The City offers numerous insights for scholarship and political action to guard against the spread of vested interest urbanism"--